The memory of the Shoah in Jewish museums : a comparative analysis of the role of the Shoah in the Jewish Historical Museum Amsterdam and the Jewish Museum Berlin - Kolbar, Natalia (Menasseh ben Israel Instituut studies, 2016)
Jewish museums cannot avoid the question of the place of the Holocaust in their presentations. When presenting the Holocaust, they are confronted with a number of challenges that ultimately define their purpose as Jewish museums. In this publication, Natalia Kolbar explores the role of the Shoah in these institutions and the implications for the presentation and interpretation of Jewish history, culture and religion, by comparing the Jewish Historical Museum in Amsterdam with the Jewish Museum in Berlin. The author examines their architecture, narrative, the manner they balance education and commemoration and how they place and convey Jewish identity in their particular Dutch and German contexts